Stress Corrosion Cracking of Stainless Steel 316L Additively Manufactured using Sinter-based and Laser-based Technologies - Santamaria Torres, Ricardo Andres (Curtin University, 2023)
Stress corrosion cracking (SCC) poses a risk to SS316L components. The solution is widely agreed to be the development of new materials or innovative manufacturing processes that create unique microstructures to improve SCC resistance. 3D printing technologies, especially Laser Powder Bed Fusion and Sinter-based Material Extrusion, are seen as promising pathways for achieving this goal. This research aims to investigate the impact of process parameters on printed microstructures to develop enhanced alloys for SCC resistance